Welfare Implications of Alternative Monetary Policy Rules: A New Keynesian DSGE Model for Turkey - Filiz Yağcıbaşı Özge; Ozan Yıldırım Mustafa (Review of Economic Perspectives, 2017)
In recent years, there has been extensive research on the conduct of monetary policy in small open economies that are subject to inflation and output fluctuations. Policymakers should decide whether to implement strict inflation targeting or to respond to the changes in output fluctuations while conducting monetary policy rule. This study aims to examine the response of alternative monetary policy rules to Turkish economy by means of a DSGE model that is subject to demand and technology shocks. The New Keynesian model we used is borrowed from Gali (2015) and calibrated for the Turkish economy. Welfare effects of alternative Taylor rules are evaluated under different specifications of central bank loss function. One of the main findings of this paper is that in the case of a technology shock, strict inflation targeting rules provide the minimum welfare loss under all loss function configurations. On the contrary, the losses are weakened if the monetary authority responds to output fluctuations in the presence of a demand shock. Finally, there exists a trade-off between the volatility of output and inflation in case of a technology shock, while the volatility of both variables moves in the same direction in response to a demand shock.
Keywords: 330; Central Bank; DSGE; Monetary Policy; Taylor Rule